Expressions of SHOX2, RASSF1A and PTGER4, and the relationship between their methylation and clinicopathological characteristics in patients with lung cancer: Methylation of SHOX2, RASSF1A, PTGER4 in Lung Cancer - Su, Haitao; Lv, Qiaoye; Wang, Limei; Hu, Jigang; Lv, Yinggang; Jia, Liting; Qi, Qingbin (Journal of Medical Biochemistry, 2024)
Background: To explore the expressions of short stature homobox2 (SHOX2), Ras-association domain family 1A (RASSF1A) and prostaglandin E receptor 4 (PTGER4), and the relationship between their methylation and clinicopathological characteristics in patients with lung cancer (LC). Methods: The surgical specimens of cancer tissues and para-carcinoma tissues were collected from 50 patients with LC in the Affiliated Hospital of Hebei University of Engineering between January and November 2023. The expressions of SHOX, RASSF1A and PTGER4 proteins in cancer tissues and para-carcinoma tissues were detected by immunohistochemistry, and methylation status of SHOX, RASSF1A and PTGER4 genes in peripheral venous blood was detected by sulfite-modified real-time fluorescence quantification. The positive expression rates of SHOX2, RASSF1A and PTGER4, and positive rates of SHOX2, RASSF1A and PTGER4 genes methylation in cancer tissues and para-carcinoma tissues were compared. The relationship between SHOX2, RASSF1A, PTGER4 methylation and clinicopathological characteristics in LC patients was compared by real-time fluorescence quantitative PCR. Results: The positive expression rates of SHOX2, RASSF1A and PTGER4 in cancer tissues were 44.0%, 54.00% and 50.00%, significantly lower than those in para-carcinoma tissues (90.00%, 96.00%, 82.00%, P
Keywords: Lung cancer; Short stature homobox2; Ras-association domain family 1A; Prostaglandin E receptor 4; Methylation; Clinicopathology